Analisis Efektivitas Konten Media Sosial dalam Meningkatkan Brand Awareness Parfum Lokal Bali: Studi Kasus Aurumsan - Nia Miftachsu Sholeha; Griffed Estonia Menanti; I Made Pradipta; Rifky Lana Rahardian; Ida Ayu Mirah Cahya Dewi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study analyzes the effectiveness of social media content in enhancing brand awareness of Aurumsan, a Balinese perfume brand that emphasizes cultural storytelling. A mixed methods approach was used, combining quantitative data from 100 respondents through a Likert-scale questionnaire and qualitative data from interviews and observations of Instagram and TikTok content. The results showed positive perceptions of content effectiveness (mean = 34.65) and brand awareness (mean = 37.08), with strong instrument reliability (Cronbach’s Alpha = 0.951). Content integrating cultural narratives and aesthetic visuals effectively enhanced emotional engagement and brand recall. Qualitative findings indicated that storytelling remains the brand’s core strategy, though challenges persist in content consistency and creative resources. It is concluded that storytelling-based social media content significantly contributes to increasing brand awareness. Future strategies should focus on improving posting consistency, expanding collaborations, and promoting user-generated content to strengthen digital marketing performance.